2021
DOI: 10.1007/s10461-021-03292-y
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Anxiety, Stress, and Substance Use Patterns During COVID-19 Pandemic in the Miami Adult Studies on HIV (MASH) Cohort

Abstract: We evaluated mental health and substance use during the COVID-19 pandemic in 196 participants from the Miami Adult Studies on HIV (MASH) Cohort. A survey was administered between July-August of 2020, including validated measures of resilience and anxiety, a scale to measure COVID-19-related worry, and self-reported substance use. Compared to HIVuninfected participants (n = 80), those living with HIV (n = 116) reported fewer anxiety symptoms, less COVID-19-related worry, and higher resilience. Those with more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
0
27
1
Order By: Relevance
“…The prevalence of methamphetamine, methylenedioxy-methamphetamine (MDMA), gamma hydroxybutyrate (GHB), ketamine, and cocaine/crack use all showed decreases. Cocaine use prevalence was also found to be lower during the pandemic, based on a survey of people recruited from the Miami Adult Studies on HIV from 32.7% between July and August of 2020, compared to 14.3% inn survey responses provided 7.3 ± 1.5 months earlier [ 29 ]. The fall in cocaine use was shown to be greater in a subgroup of participants living without HIV (41.2% to 15.0%) compared to participants living with HIV (26.7% to 13.8%) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of methamphetamine, methylenedioxy-methamphetamine (MDMA), gamma hydroxybutyrate (GHB), ketamine, and cocaine/crack use all showed decreases. Cocaine use prevalence was also found to be lower during the pandemic, based on a survey of people recruited from the Miami Adult Studies on HIV from 32.7% between July and August of 2020, compared to 14.3% inn survey responses provided 7.3 ± 1.5 months earlier [ 29 ]. The fall in cocaine use was shown to be greater in a subgroup of participants living without HIV (41.2% to 15.0%) compared to participants living with HIV (26.7% to 13.8%) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In PLWH, high resilience has been associated with lower depression and anxiety ( McGowan et al, 2017 , Thurston et al, 2018 ), improved health behaviors leading to higher ART adherence and viral suppression ( Brewer et al, 2020 , Dulin et al, 2019 , Fletcher et al, 2020 ), safer sexual practices ( McNair et al, 2017 ), and higher health-related quality of life ( Fang et al, 2015 ). In the Miami Adult Studies on HIV (MASH) cohort, PLWH exhibited higher resilience than their HIV-uninfected peers during the early months of the pandemic ( Diaz-Martinez et al, 2021 ). Additionally, higher resilience in part accounted for lower anxiety and stress in PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…As individuals have become more socially isolated and stressed, this exacerbated different mental health problems including depression and anxiety among both adolescents and adults (Cianfarani & Pampanini, 2021;Coiro et al, 2021;Czeisler et al, 2020;Diaz-Martinez et al, 2021;Magson et al, 2021). Further, consistent with GST, studies have found an increased use of alcohol and cannabis among young people and adults to cope during the pandemic (Diaz-Martinez et al, 2021;Dumas et al, 2020;Grossman et al, 2020;MacMillan et al, 2021). For example, drawing on the survey among adults in the U.S. and Canada, MacMillan et al (2021) have shown that such stressful conditions as being personally affected by COVID-19 and experiencing childcare challenges increase the risk for substance use during the pandemic.…”
Section: Stress During the Covid-19 Pandemicmentioning
confidence: 99%
“…Recent empirical studies have elaborated on the consequences of stressful conditions during the COVID‐19 pandemic. As individuals have become more socially isolated and stressed, this exacerbated different mental health problems including depression and anxiety among both adolescents and adults (Cianfarani & Pampanini, 2021 ; Coiro et al., 2021 ; Czeisler et al., 2020 ; Diaz‐Martinez et al., 2021 ; Magson et al., 2021 ). Further, consistent with GST, studies have found an increased use of alcohol and cannabis among young people and adults to cope during the pandemic (Diaz‐Martinez et al., 2021 ; Dumas et al., 2020 ; Grossman et al., 2020 ; MacMillan et al., 2021 ).…”
Section: Explanations Of the Relationship Between The Covid‐19 Pandem...mentioning
confidence: 99%